The actual french tech ecosystem's ability to create unicorns - Saleur, Erwin; Igel, Barbara; Zimmermann, Willi; Vimolwan Yukongdi; EDHEC Business School, France (2019)
In 2019, France has celebrated the birth of a new digital unicorn: Doctolib. Despite this success, some articles were published, warning that the ecosystem had trouble to provide more of those successful start-ups. On one hand, the French tech ecosystem is booming with a phenomenal increaseof the number of start-ups and investments. But on the other hand, since 20l3, only three French start-ups have managed to become unicorns, which means international market leaders. This is worrying as it could be the sign of an overvalued trend, on which France is betting its economic growth since the end of the Subprimes in 2012. The purpose of this study is to question the real potential of the French tech ecosystem. Can it create unicorns on a regular basis? Our investigation confirms that the ecosystem has the potential to do so, the only condition being to consolidate some pillars that have been let behind because of this brutal growth.
A research study submitted in partial fulfillment of the requirements for the degree of Master of Business Administration
Research Studies Project Report (M.B.A.) - Asian Institute of Technology, 2019
Keywords: Ecosystem management